Peran United Nations High Commissioner for Refugee (UNHCR) dalam Menangani Pengungsi Suriah Korban Sexual and Gender-based Violence (SGBV) di Lebanon - Shabrina, Adinda Ayu; Windiani, Reni; Basith Dir, Andi Akhmad (Journal of International Relations, 2018)
Sexual and gender-based violence is a violence directed against someone based on their gender or sex. SGBV can happen not only in times of peace but also in times of war. This is also what happens in Lebanon to the refugees from Syria. These Syrian refugees have to face and deal with sexual violence and harrassment like rape, survival sex, and early marriage. This research will analyze the roles UNHCR have in handling SGBV victims in Lebanon using the international organization theory by Clive Archer and humanitarian diplomacy concept by Larry Minear and Hazel Smith. This research aims to identify the presence of each activities of humanitarian diplomacy in Lebanon and analyze the role of UNHCR according to the international organization theory. This research uses the literature study method with 2012-2016 set as its timeframe. The result of this research is that humanitarian diplomacy activities are present in Lebanon, and UNHCR has played its role as an international organization in Lebanon.